2019
DOI: 10.1029/2019ja026757
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Relativistic Microburst Intensity From SAMPEX Observations

Abstract: Relativistic electron microbursts are an important electron loss process from the radiation belts into the atmosphere. These precipitation events have been shown to significantly impact the radiation belt fluxes and atmospheric chemistry. In this study we address a lack of knowledge about the relativistic microburst intensity using measurements of 21,746 microbursts from the Solar Anomalous Magnetospheric Particle Explorer (SAMPEX). We find that the relativistic microburst intensity increases as we move inward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…Lastly, Figure 5b shows that curtains are associated with an enhanced AE up to around 600 nT. While it is not a direct comparison (due to the electron energy channels and the binning scheme), Douma et al (2019) showed that the number of microburst observed by SAMPEX also increases with increasing AE, up to about AE = 300 nT.…”
Section: When and Where Are Curtains Observedmentioning
confidence: 94%
See 1 more Smart Citation
“…Lastly, Figure 5b shows that curtains are associated with an enhanced AE up to around 600 nT. While it is not a direct comparison (due to the electron energy channels and the binning scheme), Douma et al (2019) showed that the number of microburst observed by SAMPEX also increases with increasing AE, up to about AE = 300 nT.…”
Section: When and Where Are Curtains Observedmentioning
confidence: 94%
“…While the impact of curtains on the magnetosphere and Earth's atmosphere is unknown, the impact of microbursts has been estimated to be substantial. Lorentzen, Looper, et al (2001), Thorne et al (2005), Breneman et al (2017), and Douma et al (2019), among others, estimated that microbursts could deplete the outer radiation belt electrons in about a day. Furthermore, Seppälä et al (2018) modeled a 6‐hr microburst storm and concluded that microbursts depleted mesospheric ozone by roughly 10%.…”
Section: Introductionmentioning
confidence: 99%
“…More details on the CNA derivation (in particular the determination of the quiet-day curve) from SGO riometer observations can be found in Sect. 2.1.3 of Grandin (2017).…”
Section: Research Datamentioning
confidence: 97%
“…For this thought‐experiment, however, a constant loss‐rate is sufficient to determine the relative impact of the precipitation at different energies; a very similar approach was undertaken to investigate the long‐term impact of electron microburst precipitation on trapped electron fluxes by Douma et al. (2019).…”
Section: Impact On the Radiation Beltsmentioning
confidence: 99%
“…We note that Equation 1 is time-invariant-a more realistic approach would be to introduce some time-dependence to better model the decaying trapped flux. For this thought-experiment, however, a constant loss-rate is sufficient to determine the relative impact of the precipitation at different energies; a very similar approach was undertaken to investigate the long-term impact of electron microburst precipitation on trapped electron fluxes by Douma et al (2019). interaction time between electrons and EMIC waves is not exactly clear, as it depends not only on the energy of the electrons in question, but also strongly on the longitudinal extent of the EMIC-wave region, which is in general fairly difficult to determine, and has to date largely only been examined on a case-by-case basis (e.g., Hendry et al, 2020).…”
Section: Impact Of Emic-driven Eep On Trapped Flux Populationsmentioning
confidence: 99%